Anticholinergic burden and behavioral and psychological symptoms in older patients with cognitive impairment - Pistorio, Sabrina; Scotto di Tella, Gianluca; Canzanella, Vittoria; Merenda, Raffaella; Cuomo, Gianluigi; Iacotucci, Paola; Carnovale, Vincenzo; Bencivenga, Leonardo; Vargas, Maria; Manes, Annalaura; Cataldi, Mauro; Rengo, Giuseppe; et al. (Frontiers in Medicine, 2025)
BackgroundDrugs with anticholinergic properties are frequently prescribed to patients with cognitive impairment. The cholinergic system plays an important role in learning processes, memory, and emotions regulation. The aim of this research is to report use of anticholinergic drugs in a clinical population and to investigate the correlation between the use of anticholinergic drugs and the risk of presenting with more severe behavioral and psychological symptoms (BPSD).MethodPatients with a diagnosis of subjective cognitive impairment, mild cognitive impairment (MCI) or dementia were recruited. Screening tests for cognitive impairment (MMSE) and functional status (ADL, IADL) were performed. BPSD were evaluated with the Neuropsychiatric Inventory (NPI). The anticholinergic burden was calculated using the ACB calculator. We compared patients at low risk of anticholinergic adverse effects (ACB < 3) versus patients at high risk (ACB ≥ 3). Chi-square test and Mann–Whitney test were used to compare the two groups. A multiple linear regression was performed to identify factors associated with higher NPI score and a logistic regression model was built to identify drug classes associated with ACB ≥ 3.ResultA total of 173 patients (mean age 74 ± 7, 74 men) were included in the study; 132 patients with ACB < 3 (low risk) versus 41 patients with ACB ≥3 (high risk) were compared. No statistically significant differences were found between the two groups in terms of demographics (age, sex) and anamnestic variables (education, marital status, family history of dementia, hypertension, diabetes, smoking, dyslipidemia, atrial fibrillation, coronary heart disease and use of alcohol). Significantly higher NPI scores were found in patients with ACB ≥ 3 (mean scores 47.3 ± 34.8 versus 25.5 ± 24.6, p < 0.001). Patients with ACB ≥ 3 showed lower MMSE (18.5 ± 8.6 versus 22.4 ± 7, p = 0.004) and more IADLs lost. In the multivariate regression analysis, after adjusting for age, sex, polypharmacy and IADLs lost, only the MMSE and the ACB scores were independent predictors of the NPI score. Being on antipsychotics, antidepressants and antidiabetic drugs was associated with increased risk of higher anticholinergic burden.ConclusionIn conclusion, the anticholinergic burden might play a significant role as a risk factor for developing more severe BPSD in patients with cognitive decline, independently from their degree of cognitive impairment.